Capital Income Taxation and Household Production - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2015)
The Atkinson-Stiglitz Theorem and its extensions have been interpreted as implying that capital income should not be taxed. If, as seems reasonable on empirical grounds, we introduce production of household goods with close market substitutes, this conclusion no longer holds. We analyse optimal capital income taxation for this case.
Keywords: H22; D13; 330; optimal capital taxation; household production